Efeito do Manejo Sobre a Produção e Composição Química de Perfilhos do Capim-Colonião (Panicum maximum Jacq.) - Ezequiel, Jane Maria Bertocco [UNESP]; Favoretto, Vanildo [UNESP] (My University, 2000)
The effects of cutting frequency of 28, 35 and 42 days, performed in December, January and February at 0 cm, 15 cm and 30 cm from the ground on the chemical composition and tiller production of Panicum maximum Jacq were assayed. The experimental area was fertilized during the sowing, at uniform cuttings. Dry matter yield was the main factor affecting the nutrients production by area. The crude protein content of tillers showed no linear response to the cutting interval and sensitively decrease at low cutting height and high cutting frequency. The ADF concentrations of tillers exhibited small variation within the interval of growth period studied of 28 to 42 days. The best management for Panicum maximum could be at 42 days cutting frequency at 15 cm from the ground.
Effect of Management on the Chemical Composition and Tillers Production of Colonião Grass (Panicum maximum Jacq.)
Keywords: Cutting frequency; Cutting height; Panicum maximum; Protein; Tiller; Year season